Supporting active learning opportunities with feedback enhances student achievement in pharmaceutical innovation module: Implication of behavioural and cognitive engagement - Taher Hatahet (Social Sciences and Humanities Open)
This study delves into the application of the engagement constructs of Fredricks et al., and the provision of feedback in online remote learning environments. Focusing on Virtual Learning Environments (VLEs) as the primary access points for module resources and analysing students' browsing patterns, it was observed that students primarily accessed the final module assignment pages of these VLEs, indicating a strategic learning behaviour with a focus on grades. Attendance at active learning lectures significantly boosted final module grades, highlighting the impact of interactive learning experiences on academic achievement. Additionally, optional “assignment'outline” submissions, coupled with individualised feedback, significantly enhanced student performance, underscoring the importance of self-regulation and metacognitive development in academic success. This study underscores the multidimensional nature of engagement and the efficacy of diverse engagement pathways in facilitating academic achievement in online remote learning contexts.